Measurement Method of the Grain Quantity Based on The Ground Pressure - Fan Chao; Zhang Dexian; Yang Tiejun; Fu Hongliang (Institute of Advanced Engineering and Science, 2014)
To measure the stored grain quantity accurately and reliably, the measurement method based on the ground pressure is put forward. According to the randomness of the granary pressure distribution caused by the limited fluidity of the grain, the layout of the pressure on the ground is set up, and the mean pressure on the ground is used to represent the whole ground pressure. At the same time, the pressure distribution on the wall is analyzed and the compensation method is given, which can reduce the sensors used in this method and the cost is low. Lastly, the estimation model of the stored grain quantity based on the ground pressure is put forward, to improve the prediction accuracy of the grain weight, the parameters are estimated based on the ratio of the error. The experiment results shown that, the measurement error is less than 3% by using this method, which can meet the actual need of real-time online monitoring the national grain storage quantity and distribution effectively.